INITIAL COURSE DESIGN PHASE OF GROUP WORK EDUCATION USING AUTHENTIC E-LEARNING - Roshini Pillay (Stellenbosch University, 2021)
Group work education develops student competences for praxis. The Authentic eLearning framework has the potential to strengthen course design, develop critical thinking, multiple perspectives, articulation and reflection. This qualitative study conducted using educational design research explored the pedagogical practices of South African social workers in group work education. Ethics clearance for this study was received and data were analysed using content analysis. Findings identified educator strategies including the use of real-world context, reflection and group collaboration, but the study noted the potential for incorporating technology-enhanced learning. Extrapolating from this study, opportunities for educators in this field during the Covid-19 pandemic are indicated.